2001
DOI: 10.1083/jcb.200106025
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of MAP2 and MAP1B knockout in neuronal migration, dendritic outgrowth, and microtubule organization

Abstract: MAP1B and MAP2 are major members of neuronal microtubule-associated proteins (MAPs). To gain insights into the function of MAP2 in vivo, we generated MAP2-deficient (map2−/−) mice. They developed without any apparent abnormalities, which indicates that MAP2 is dispensable in mouse survival. Because previous reports suggest a functional redundancy among MAPs, we next generated mice lacking both MAP2 and MAP1B to test their possible synergistic functions in vivo. Map2 − /−map1b −/− mice died in their perinatal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
209
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(222 citation statements)
references
References 50 publications
12
209
1
Order By: Relevance
“…Consistently, antisense depletion of MAP2 inhibited neurite initiation [35]. However, other work showed that contact-induced neurite formation in sympathetic neurons still took place in the presence of microtubule stabilizing/destabilizing pharmacological agents [36], and that neurite initiation still occurred in mice double knockout for MAP2 and MAP1B [37], suggesting alterative/redundant mechanisms for neurite initiation. Based on the ability of MAPs to interact with actin, coordination between the two cytoskeletal structures has been proposed to mediate neurite initiation [38,39].…”
Section: Introductionmentioning
confidence: 79%
“…Consistently, antisense depletion of MAP2 inhibited neurite initiation [35]. However, other work showed that contact-induced neurite formation in sympathetic neurons still took place in the presence of microtubule stabilizing/destabilizing pharmacological agents [36], and that neurite initiation still occurred in mice double knockout for MAP2 and MAP1B [37], suggesting alterative/redundant mechanisms for neurite initiation. Based on the ability of MAPs to interact with actin, coordination between the two cytoskeletal structures has been proposed to mediate neurite initiation [38,39].…”
Section: Introductionmentioning
confidence: 79%
“…Slides were analyzed using Olympus (Tokyo, Japan) IX-71 microscopy using a 10ϫ objective. For quantitative measurements, comparable sections were chosen at the somatosensory cortex, which was divided into 10 horizontal bins from the superficial to the deep, and labeled nuclei in each bin were counted (Teng et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Tau, which is preferentially found in axons (Binder et al, 1985), and MAP2, which is preferentially found in dendrites (Bernhardt and Matus, 1984), might bundle MTs because overexpression of these proteins in insect cells generates processes that have MT-MT spacings that reflect the size of the MAP (Chen et al, 1992). Nonetheless, mice lacking either tau or MAP2 have relatively normal neurons, which suggests that other factors are involved (Harada et al, 1994;Teng et al, 2001). Motor proteins, which help bundle MTs in S. pombe and plant cells, are other likely candidates.…”
Section: Mt Bundlingmentioning
confidence: 99%